Rural Development Trajectories in Eastern India: Empirical Insights from Purba Medinipur District, West Bengal - Ahmed Nizamuddin (Social Empowerment Journal, 2025)
This study examines the socio-economic conditions and infrastructural access of rural households in Purba Medinipur district, West Bengal, through a detailed field survey conducted across 33 villages in 11 administrative blocks between November 2024 and June 2025. A total of 825 households, representing a population of 2,540 individuals, were surveyed using a structured questionnaire and purposive sampling method. The research adopts a mixed-method approach, combining quantitative analysis of household-level indicators with qualitative thematic interpretation based on field observations.The findings reveal significant advancements in areas such as electrification (97.69%), private toilet usage (97.69%), and mobile phone penetration (98.33%). However, the study also highlights critical gaps in waste collection services, drainage infrastructure, access to clean water, and the availability of modern appliances such as refrigerators and computers. The use of traditional fuels persists in many homes despite a growing shift towards LPG. Based on the results, the study recommends targeted interventions to strengthen sanitation, promote clean energy, improve digital access, and expand sustainable infrastructure through decentralized planning.This research provides valuable, ground-level insights for policymakers, development practitioners, and local governance bodies seeking to promote inclusive and sustainable rural development.